Role of phytochemicals in cardiovascular disease management: Insights into mechanisms, efficacy, and clinical application - Esther Ugo Alum (Elsevier, 2025)
Background/Objective: New approaches to prevention and treatment are necessary for cardiovascular diseases (CVDs), a major worldwide health issue. Phytochemicals and bioactive compounds of plant origin have attracted much interest due to their potential role in reducing the risk of cardiovascular diseases. This review article aims to discuss phytochemicals in CVD management, including their mechanisms of action, benefits, and applications in detail. The review analyzes findings from clinical trials, epidemiological studies, and preclinical research to explain how these phytochemicals are effective in preventing and treating cardiovascular diseases. We also consider limitations, including phytochemical bioavailability, the appropriate dosage, and possible combinations with other treatments. Methods: The data for the review were obtained from articles in peer-reviewed journals, clinical trials, systematic reviews, meta-analyses, and other studies published within the last decade. A thorough search was conducted in four databases: PubMed, Scopus, Web of Science, and Google Scholar, using keywords such as phytochemicals and CVDs. Results: In this study, polyphenols, carotenoids, glucosinolates, saponins, and tannins, were the various classes of phytochemicals. Multiple mechanisms, such as combating oxidative stress, controlling inflammation, enhancing the function of endothelial cells, regulating lipid levels, preventing platelet clot formation, and managing blood pressure, have demonstrated the cardiovascular benefits of these phytochemicals. The study highlights most prominent phytochemicals such as flavonoids (e.g., quercetin, catechins), carotenoids (e.g., lycopene, beta-carotene), and glucosinolates (e.g., sulforaphane), all of which have significant roles in enhancing cardiovascular health. Conclusion: The current evidence suggests that phytochemicals could significantly contribute to the prevention and treatment of CVDs through dietary and therapeutic interventions.